DESENVOLVIMENTO, CARACTERIZAÇÃO E APLICAÇÃO DE SISTEMAS NANOESTRUTURADOS CONTENDO ÁCIDO ASCÓRBICO E PALMITATO DE ASCORBILA EM HAMBURGUERES DE CARNE BOVINA - Favarin, Fernanda Reis (2021)
Ascorbic acid (AA) and ascorbyl palmitate (PA) can be used in meat products, such as hamburgers, with the function of antioxidants, as they prevent lipid oxidation. However, AA and AP are unstable due to several extrinsic factors, such as temperature, light, oxygen, the presence of metals, among others. Thus, these compounds can be protected through nanotechnology, with the association in liposomal vesicles. However, these vesicles are obtained in a liquid medium, which limits their stability and makes their application difficult. This adversity can be overcome through strategies such as the conversion of these suspensions into powdery systems or the incorporation in gelatinous films, both of which can be used to try to prevent the lipid oxidation in meat products. Thus, this work aims to develop, characterize, and apply nanostructured systems containing AA and PA as a bioadditive in meat products. Initially, a chromatographic method was developed and validated for the simultaneous determination of AA and PA in liposomes, this method proved to be adequate, in accordance with the legislation. After validation, studies of pre-formulation, characterization, stability, antioxidant, antimicrobial activity in vitro safety profile in healthy human cells of AA and PA-containing liposomes. The liposomes initially had an average vesicle diameter of 156 nm, an IPD of 0.202, a zeta potential of -32.3 mV, a PA content of 0.94 mg/mL and 0.97 mg/mL of AA, 3.30 of pH, antioxidant activity of 39.4 mol TE/mL, and spherical morphology. In addition, the formulations did not show antimicrobial activity against the tested bacteria and fungi and did not demonstrate toxicity in in vitro tests. The stability of the liposomes varied according to the temperature at which they were stored, being more stable under refrigeration (± 4 ºC) and less stable in a climatic chamber (± 40 ºC). In a second stage of the work, the liposomal formulation was spray-dried using the spray dryer, using lactose as an adjuvant (10 %), it was characterized, and its stability, antioxidant activity and in vitro safety profile was determined. Still, after these tests, the incorporation of the dry formulation in beef burgers was carried out and the antioxidant activity of the powdery systems was analyzed against the lipid oxidation of cooked hamburgers packaged in aerobic medium. After spray drying, it was possible to notice that the liposomal vesicles did not undergo unexpected physical-chemical changes resulting from the drying process, which showed a yield of 72.3%. The powdered liposomal systems after aqueous redispersion had a vesicle size of 146 nm, IPD of 0.248, zeta potential of -25.5 mV, 3.40 of pH, content of 0.91 mg/mL for PA and 0.89 mg/mL for AA, antioxidant activity of 26.3 mol TE/mL and spherical morphology. Powdery liposomal systems did not demonstrate cytotoxicity in fibroblasts according to the safety tests analyzed. The content and physicochemical characteristics of the dry formulation remained more stable and better when compared to the liquid formulation, at the temperatures analyzed (climatic chamber – ± 40 ºC and room temperature – ± 25 ºC). In addition, the liposomal powdered systems have been shown to decrease the lipid oxidation of cooked hamburgers stored under refrigeration for 6 days, compared to hamburgers prepared with free actives. In the third stage, to fulfill the second strategy of stabilization and application of the liposomes developed in this work, the liquid formulation was incorporated into gelatinous films, which were characterized and adhered to corona-treated packaging. The films had a thickness that ranged from 44.2 to 48.9 μm, and the film that was incorporated with liposomes containing ascorbic acid and ascorbyl palmitate showed an in vitro antioxidant activity of 21.22 mg TE/g of film. The antioxidant activity of the films and packaging was analyzed against the lipid oxidation of hamburgers (raw and cooked) packaged in an aerobic medium and under vacuum, under refrigeration. The films and packaging containing the films incorporated with liposomes proved to be effective in reducing the lipid oxidation of cooked hamburgers stored under refrigeration in an aerobic medium for 6 days, in relation to the other treatments. Corona-treated packaging and adhered films, on the other hand, have been shown to delay the lipid oxidation and to decrease the loss of meat pigment in raw hamburgers, stored for 14 days under refrigeration and vacuum, demonstrating to be a promising alternative for the meat products segment. Through the results found, it was possible to develop, characterize and apply nanostructured systems containing ascorbic acid and ascorbyl palmitate as a bioadditive potential in meat products, in order to reduce the sodium content in these products.